The Importance of Hardiness For Students In 21st Century - Rakhmi, Rissa Fadhilla; Solehuddin, Solehuddin; A, Anne Hanifa (International Conference on Elementary Education, 2020)
21st Century Learning is a learning process that integrates literacy skills, knowledge skills, skills and attitudes and also mastery of technology. Learning in the 21st Century has an impact on changing lives that are growing dynamic and complex. This very dynamic change in life also turns out to increase various complex problems for students, including those related to psychological problems, not just about academic problems. This study aims to examine the literature on the importance of hardiness for students in the 21st Century. Hardiness is important for students because students as teenagers have complex problems. Students are faced with life's challenges that are complex enough as they are prepare themselves to become physically and psychologically healthy. In addition to various complex problems faced by students, in the 21st century students as teenagers are also faced with intense competition so that young people are required to have high competitive power to be able to excel and succeed in actualizing themselves. These things can be a source of stress for students if they cannot cope with the stress they face. Hardiness is a personality characteristic that makes an individual have confidence that he can deal with various things and help to control the various effects of stress on life that occurs. The hardiness aspect consists of control, commitment and challenges